Bibliometric analysis of health-related quality of life in adolescents with type 1 diabetes - Martín-Ávila, Javier; Rodríguez-Jiménez, Esther; Pérez-Marín, Marián; Valero-Moreno, Selene (Frontiers in Pediatrics, 2025)
Type 1 Diabetes Mellitus (T1DM) affects an estimated 8.75 million individuals worldwide and commonly emerges during adolescence—a critical developmental stage marked by significant physical and psychological changes. The intersection of T1DM and adolescent development can substantially impact both mental and physical health. As a result, interventions aimed at addressing this impact often utilize the concept of health-related quality of life (HRQOL) to evaluate their effectiveness. This study aimed to identify major trends, influential authors and institutions, and leading journals in the scientific literature related to HRQOL in adolescents with T1DM, based on publications indexed in the Web of Science database. A bibliometric analysis was conducted using the Web of Science database, yielding 231 relevant articles published between 2003 and 2024. The data were analyzed to determine publication trends, geographic distribution of research activity, key contributors, and thematic evolution based on keyword analysis. The results revealed a recent surge in the production of these articles, with the United States and Germany emerging as the countries where this field is most extensively studied, collectively accounting for nearly 40% of the total output. Several authors, institutions, and journals were identified as particularly influential in this area of research. Keyword analysis suggests a paradigm shift within literature from a primarily clinical focus to a broader, multidimensional approach that emphasizes psychosocial factors, family dynamics, and self-management strategies. This trend reflects an evolving understanding of the complex interplay between disease management and quality of life in adolescents living with T1DM.